To show the Distributive Property, we start with the equation:
\[ 7(2 + 4) = 14 + x \]
First, we calculate the left side of the equation using the Distributive Property:
\[ 7(2 + 4) = 7 \times 2 + 7 \times 4 \]
Calculating each term:
\[ 7 \times 2 = 14 \] \[ 7 \times 4 = 28 \]
Now, adding those results together:
\[ 14 + 28 = 42 \]
So we have:
\[ 7(2 + 4) = 42 \]
Now we can set the right side equal to 42:
\[ 42 = 14 + x \]
To find \( x \), we subtract 14 from both sides:
\[ x = 42 - 14 \] \[ x = 28 \]
Thus, the value that can replace \( x \) is \( \boxed{28} \).